ON INTERMEDIATE HEADCOUNT INDICES OF POVERTY. (14th July 2017) - Subramanian, S.; Mukherjee, Diganta
ABSTRACT: The archetypal population‐relative measure of poverty is the Headcount Ratio, while the archetypal population‐absolute measure is the Aggregate Headcount. The overwhelming emphasis in the poverty measurement literature has been on population‐relative measures. The value‐basis for this preference has been seldom submitted to serious scrutiny, with the result that absolute and intermediate measures have generally been subjected to relative neglect. There would appear to be a strong case for the employment of indices which are intermediate between relative and absolute measures, and which avoid the extreme values underlying both. The present note, building on earlier work by scholars such as Arriaga, Krtscha, Del Rio, Alonso‐Villar, Mukherjee, Zheng and Zoli, aims to advance the cause of a workable and plausible population‐intermediate headcount index of poverty.